Epidemiological, Clinical and Etiological Aspects ofSciatica in Hospital Setting, CNHU-HKM Cotonou - ADJIEN, KODJO CONSTANT; GNONLONFOUN, DIEU-DONNÉ; DOCHAMOU, CYRIAQUE; ACCROMBESSI, DONALD; HOUINATO, Dismand (My University, 2018)
Sciatica, mostly clinical-based diagnosis, is a potentially debilitating condition as a result of disco-radicular contlict between L4 and L5 or Ls and SI' This study aims at describing the epidemiological, c1inical and etiological aspects of sciatica in Hubert Koutoukou Maga Teaching Hospital (CNHU-HKM) of Cotonou. It was a prospective, descriptive and analytical study conducted in CNHU-HKM Cotonou neurology department from pt January to 30th June 2016. The study population comprised 115 low back pain patients seen in consultation. Data collection was carried out through a standard information sheet with socio-demographic, clinical, para·c1inical, etiological and therapeutic data. Epi data 3.1 was used for data entry and Statall for processing. Frequency of sciatica was 18.6%, with 95% CI [11.5% -25.7%]. The study population age ranged from 29 to 73 years, with 52 ± 16 as mean value, while sex ratio was estimated at 0.6. Bilateral sciatica representing 53% was present in Ls and SI nerve roots in 44.4% of cases. It was exacerbated in prolonged standing (24.4%) and relieved in supine position (44.3%), with paresthesia (59.1%) and intermittent radicular claudication (40.9%). Spinal osteoarthritis was the most prevalent etiology (47%). Sciatica is becoming increasing prevalent and should he regarded as problem ofhealth concern.
Keywords: Sciatica; Prevalent; Cotonou